Mass dependent isotopic fractionation of molybdenum in the solar system - Liang, YH (2013)
Mass dependent isotope fractionation of stable isotopes between meteorites and planetary materials has been used to assess processes that occurred during formation of Earth and its core. However, thus far little is known about the mass dependent isotope fractionation of Mo in the solar system, and at high temperatures in the Earth, in particular during mantle processes. Molybdenum is a refractory and moderately siderophile element. The processes that might have fractionated Mo in the early solar system include condensation and evaporation of dust grains, metal-silicate segregation, core crystallization, silicate and sulphide melting and aqueous alteration. In order to investigate the processes fractionating Mo isotopes, it is first necessary to assess how much fractionation takes place during mantle melting, estimate the isotopic composition of the bulk silicate Earth, and then make comparisons with primitive and differentiated meteorites. I present double spike Mo isotope data for forty-two mafic and seven ultramafic samples from diverse locations, and nineteen extra-terrestrial samples. The delta98/95Mo values of all the terrestrial samples (normalized to NIST SRM 3134) exhibit a significant range from +0.53±0.21 to -0.56±0.09‰. The compositions of mid-ocean ridge basalts (MORBs) (+0.03±0.07‰, 2s.d.) and ultramafic rocks (+0.38±0.15‰, 2 s.d.) are relatively uniform and well resolved, providing evidence of fractionation associated with partial melting. In contrast intraplate and ocean island basalts (OIBs) display significant variability within a single locality from MORB-like to strongly negative (-0.56‰). The most extreme values measured are for nephelinites from the Cameroon Line and Trinidade, which also have anomalously high Ce/Pb and low Mo/Ce relative to normal oceanic basalts. The observed relationships between delta98/95Mo and Ce/Pb, U/Pb and Mo/Ce provide evidence that sulphide plays a critical role in retaining Mo in the mantle and fractionating its isotopic composition in basaltic magmas. If residual sulphides are responsible the Mo isotopic composition, Mo budget of the bulk silicate Earth will be misrepresented by values estimated from basalts. On this basis a revised best estimate of the Mo content in the bulk silicate Earth (BSE) ranging between 251 to 268 ppb is derived, approximately 6 times higher than previously assumed, and similar to the levels of depletion in refractory siderophile elements such as W, Ni and Co. This significantly ameliorates the argument for Mo removal via late stage sulphide extraction to the core. The Mo isotopic composition of the BSE (0.35‰) is distinct from the delta98/95Mo values found in primitive and iron meteorites. Although Mo isotopic fractionation varies between different phases within a single iron meteorite, and occurs during fractional crystallization in asteroidal cores, most iron meteorites have ddelta98/95MoSRM3134 (-0.14 to -0.06‰) that are similar to ordinary and CI carbonaceous chondrite (-0.12 to -0.09‰). This range of delta98/95Moo is not only significantly lighter than the BSE, but also enstatite chondrites, which have delta98/95Mo values of 0.04 to 0.13‰. Several possible explanations are proposed. (A) Core-mantle differentiation fractionates Mo isotopes. The recently proposed Mo effect of sulphide liquid removal is likely to be minor because this should have generated a light Mo isotope composition for the BSE. However, isotopic fractionation associated with metal-silicate partitioning may be responsible for the heavy Mo in the BSE. (B) A distinct isotopic composition for the late material that contributed Mo to the BSE. Enstatite chondrites (or other putative groups of chondrites with a heavy Mo isotope composition) and sulphur-rich components form the cores of impacting bodies are the most likely candidates that could deliver heavy Mo to Earth. (C) The Mo isotopic composition of the Solar System is heterogeneous in a mass dependent fashion such that heavier Mo isotopes are enriched in the section of the disk from which Earth accreted. There are some difficulties behind each of these models and further work is needed to determine which is correct.